Jihad Konstitusi dan Rekonstruksi Indonesia Berkemajuan: Strategi Advokasi Hukum Muhammadiyah dalam Menghadapi Ekstraksi Eksploitatif Sumber Daya Alam di Era Neoliberalisme - Evi Dwi Hastri; Absori Absori (TADHKIRAH: Jurnal Terapan Hukum Islam dan Kajian Filsafat Syariah, 2026)
This study is motivated by the proliferation of regulations that facilitate the exploitative extraction of natural resources in Indonesia as a consequence of the penetration of neoliberal ideology, which deviates from the mandate of Article 33 of the 1945 Constitution of the Republic of Indonesia. The significance of this research lies in the strategic role of Muhammadiyah through the "Constitutional Jihad" movement in restoring state sovereignty over natural resources for the benefit of the public welfare. The study aims to analyze the philosophical foundations of Constitutional Jihad in reconstructing the vision of a Progressive Indonesia (Indonesia Berkemajuan) and to examine Muhammadiyah’s legal advocacy strategies in resisting the hegemony of liberal economic policies. The research focuses on how Muhammadiyah’s philosophical framework and litigation strategies are capable of correcting national energy policies, as reflected in Constitutional Court Decision Number 36/PUU-X/2012. This research employs a normative legal method using statutory, case, and theological-ideological approaches. The findings reveal that, philosophically, Constitutional Jihad represents the transformation of Al-Ma’un theology and the concept of Darul Ahdi wa Syahadah into a constitutional framework that integrates divine sovereignty with popular sovereignty. In terms of strategy, Muhammadiyah utilizes Public Interest Litigation supported by interdisciplinary expert collaboration and moral mobilization rooted in civil society. The analysis of Constitutional Court Decision No. 36/PUU-X/2012 demonstrates that Muhammadiyah’s advocacy successfully invalidated unconstitutional provisions of the Oil and Gas Law that had weakened state control, while simultaneously reaffirming the state's direct management function over natural resources. The study concludes that Constitutional Jihad constitutes an effective form of national ijtihad in reconstructing a progressive, sovereign, and socially just legal order in Indonesia.